Pharmacological Activity and Clinical Use of PDRN - Squadrito, Francesco; Bitto, Alessandra; Irrera, Natasha; Pizzino, Gabriele; Pallio, Giovanni; Minutoli, Letteria; Altavilla, Domenica (Frontiers in Pharmacology, 2017)
PDRN is a proprietary and registered drug that possesses several activities: tissue repairing, anti-ischemic, and anti-inflammatory. These therapeutic properties suggest its use in regenerative medicine and in diabetic foot ulcers. PDRN holds a mixture of deoxyribonucleotides with molecular weights ranging between 50-1500 KDa, it is derived from a controlled purification and sterilization process of Oncorhynchus mykiss (Salmon Trout) or Oncorhynchus keta (Chum Salmon) sperm DNA. The procedure guarantees the absence of active protein and peptides that may cause immune reactions. In vitro and in vivo experiments have suggested that PDRN most relevant mechanism of action is the engagement of adenosine A2A receptors. Besides engaging the A2A receptor, PDRN offers nucleosides and nucleotides for the so called “salvage pathway”. The binding to adenosine A2A receptors is a unique property of PDRN and seems to be linked to DNA origin, molecular weight and manufacturing process. In this context, PDRN represents a new advancement in the pharmacotherapy. In fact adenosine and dipyridamole are non-selective activators of adenosine receptors and they may cause unwanted side effects; while regadenoson, the only other A2A receptor agonist available, has been approved by the FDA as a pharmacological stress agent in myocardial perfusion imaging. Finally, defibrotide, another drug composed by a mixture of oligonucleotides, has different molecular weight, a DNA of different origin and does not share the same wound healing stimulating effects of PDRN. The present review analyses the more relevant experimental and clinical evidences carried out to characterize PDRN therapeutic effects.